USE OF COMPUTER ANALYSIS OF OCCLUSAL CONTACTS IN ORTHOPEDIC PATIENTS WITH SECONDARY DEFORMITIES OF DENTITION (LITERATURE REVIEW) - O.V. Fedorova (Ukrainian Medical Stomatological Academy, 2017)
In patients with orthopedic secondary deformations of dentition (SDD) is often needed to change the shape of crowns of teeth, the ratio of dentition and jaws. Optimal occlusion ratio is important for the quality restoration of dentition. To improve the results of orthopedic treatment of patients with SDD it is necessary to control occlusal relationships at all stages of treatment, and the results should be stored, compared and analyzed. Studying the issues of diagnosis and treatment of patients with secondary deformities of dentition (SDD) we met the need to study the occlusal relationships. Modern stomatology uses different methods to research interocclusal correlations of teeth and jaws. For long time the main material for determining occlusal relationships was the articulation of a paper. Now This method is the most commonly used, but significant drawback of this method is the inability to record and store the data, biometric study of occlusal contacts, so far modern researchers recommend qualitative assessment of the value of the jaws to other methods of occlusal analysis. The aim of this work is to review literary sources in relation with the problems of modern technologies application, in particular, computer complex " T - Scan" for determination functional violations of dentition mobility, study of occlusal correlations, and possible spectrum of application of this software in the clinic of orthopaedic stomatology to treat patients with secondary dentitions deformations. From 1987 a "Tekscan" enterprise (THE USA) produces "T-Scan" vehicle. This system is a stomatological device, that is used for the analysis of relative occlusal forces, that registers oneself intromouth method by means of touch-control that measures the degree of pressure. Information is stored on a hard disk and can be used for an analysis step by step by means of video with a sentinel criterion. This system can measure efforts taking into account, time to estimate occlusion dynamics directly in the oral cavity of patient, which is the most exact and rapid method. System of computer analysis" T - Scan" gives possibility to conduct the exact analysis of force of occlusal contacts to define time of their origin to 0,003 second, to recreate the results graphically 2nd or 3rd diagrams [1, 2, 3, 14, 17, 19]. Data of the practical use of T - Scan specify on statement that even the perfect balanced occlusion can contain the components of functional overload, which not always can be educed on usual methodology. From data of Carey J.P., Kerstein R.B., Craig M.(2013)articulatory paper not able valuably to represent force of the occlusal loading, but computer-assisted occlusal analysis reveals actual nature of forces of occlusal contact and it was well-proven by them by means of experimental laboratory researches [2,18]. During a scan-out in the turboschedule a sensor conducts 3000 records in a second, as a result it is possible to get video of high quality, that can be watched in the slow time mode. Such dynamic recreation divides all elements of the occlusal loading in contact and simultaneous estimates their value, in order that a doctor was able to learn them and accept most at an active decision. It can be played forward or back, real-time or, 003 seconds, creating a "occlusal film" the pictures of 0. In a 3D mode a doctor sees the columns of occlusal force, in 2nd contours that present the zones of the occlusal loading, which can change the size and color. Warm colors mark greater force, cold -little ones. There is, also a chart of the total occlusal loading, which allows to estimate work of masseters, and to define balance of occlusion in relation to parts. The analysis of the material studied shows: the system of computer analysis of T - Scan gives objective data in relation to pressure, force, time of occlusal contacts, their sequence, allows exactly determine the locations of origin of occlusal overloads, compare loading from right and left parts of jaws, to determine the state of masseters[1,2,3,5,6,13,20]. The "T- Scan" software allows the doctor to write down, to look and analyze data on the occlusion of patient, to get clear demonstrative images, that represent clinical presentation and allow evidently to reveal a character that dental crowns closing changes exactly, loading is distributed and etc. To increase the level of diagnostics and treatment of occlusal violations for patients from SDD it is necessary to apply computer methodology of T - Scan, study as an analysis of contacts of teeth is qualificatory and it must be conducted on all stages of treatment and been done if possible.